Mechanical and wear behaviour of poly(vinylidene fluoride)/clay nanocomposite - Gaur, A.; Rana, D.; Maiti, P. (Elsevier Editora Ltda, 2019)
Poly(vinylidene fluoride) (PVDF)/organically modified nanoclay composites using different amount of nanoclay have been prepared through solution route. The structural changes are determined through X-ray diffraction and Fourier transform infrared spectroscopy studies, which show the transformation from α to b-phase crystallization in presence of nanoclay. Polarised optical microscopic images show the changes of spherulite pattern into mesh like pattern in presence of nanoclay. Modulus of PVDF-nanocomposite increase with increasing the nanoclay content up to 4 wt.% and then slightly decreases under uniaxial tension and the improvement in mechanical responses are fitted with theoretical models. Tribological behaviour of PVDF nanocomposites is evaluated and found that nanoclay content upto 4 wt.% is effective in decreasing the wear and coefficient of friction of PVDF. Similarly, hardness of the nanocomposites also increases for clay content upto 4 wt.%. The nanoclay is working as reinforcing agent for PVDF and is improving its mechanical and frictional properties. © 2019 The Authors.
Keywords: PVDF; Wear; Hardness; Morphology